The Use of Online Education by the Czech Population in the European Context - Bobáková, Hanne-Lore; Chylková, Martina (International Journal of Research in E-learning, 2021)
The article deals with online educational courses in the Czech Republic. The subject of the investigation is the participation of individuals between 16–74 years of age in online education in the Czech Republic and its development. The investigation also focuses on the computer skills of individuals and their development between 2005–2014, and also in 2017, depending on data availability. All the above-mentioned indicators were analysed and compared to the situation in the neighbouring countries and in the European context. The methods of analysis, synthesis and comparison were applied. The research showed that the number of individuals participating in courses in the Czech Republic was relatively low in comparison to other neighbouring countries, even though the advancement of computer skills in the Czech Republic was constantly increasing from 2005 to 2014.